Obesity and the Abdominal Wall Vasculature: Correlating BMI with Perforator Anatomy - DelMauro, Matthew A.; Moon, Victor A. (Journal of Reconstructive Microsurgery, 2020)
Background Given the national trends in obesity, reconstructive surgeons are faced with an increasing number of overweight and obese women interested in postmastectomy breast reconstruction. While the link between obesity and adverse postoperative outcomes is well established, few studies have explored the relationship between body mass index (BMI) and the vasculature of the anterior abdominal wall.Methods A radiographic review was conducted on female patients who underwent computed tomographic angiography (CTA) of the anterior abdominal wall. CTA studies were evaluated for perforator caliber and quantity. Patients were stratified by BMI. The relationship between BMI and the diameter and number of deep inferior epigastric artery (DIEA) perforators was analyzed using analysis of variance using Minitab software with α of 0.05.Results There were a total of 916 hemiabdomens included in this study. There was no statistically significant correlation between BMI and DIEA diameter or mean diameter of major (≥ 1 mm) DIEA perforators. There was a statistically significant negative correlation between BMI and the number of major DIEA perforators (p < 0.01).Conclusion Despite the increased demands of excess abdominal adiposity, DIEA perforator caliber was not correlated with BMI on CTA. The number of major DIEA perforators visualized on CTA decreased with increasing body weight may indicate a limitation of CTA for presurgical planning of abdominal free flaps in obese patients.
Keywords: deep inferior epigastric artery; body mass index; computed tomographic angiography